The impact of applying distributed leadership and charismatic leadership on organizational cynicism: applied study on the Egyptian travel agents - Alramidi, Bassam (Finance and Business Economies Review, 2019)
The study aimed to identify the effect of applying distributed leadership and the charismatic leadership on the organizational cynicism of the Egyptian travel agents' employees. To achieve the objective of the study, the researcher distributed 450 survey forms to a sample of employees in the Egyptian travel agents category "A" in the Greater Cairo. Only 407 valid forms for analysis using SPSS V.25 and SAS V.9.1. The study found that the Egyptian travel agents apply distributed leadership and charismatic leadership, as well as they have a low level of organizational cynicism. The study also found that applying distributed leadership and charismatic leadership has a significant and negative impact on the organizational cynicism of the employees of these agents.